Money, coinage and colonialism
1 online resource
Keywords: "This book explores coinage and related object types as an important form of material culture that is crucial to interrogating interactions between coloniser and colonised. Money, Coinage and Colonialism is a much overdue treatment of coinage and money in debates around ancient and recent colonial practices. It argues that coinage offers unique opportunities to study interactions and effects of the meeting between colonisers and colonised, as well as the economic, political and ideological interactions between colonial communities and the state of origin. It is argued that the study of coins and other means of exchange may reveal less apparent and under-communicated processes, values and discourses in the study of colonial environments and projects, with commonalities informing a larger "global history" approach. A broad picture is built from numerous case studies, spanning from Classical Greek colonies to European colonial enterprises of the Modern period, exploring colonial histories, settings, ideology and resistance. Particular attention is paid to the role of coins in identity construction; to ambiguity, hybridity and creolisation of monetary objects in colonial contexts; and to specific uses of coins that tell of violence, oppression and resistance as well as of networks, acculturation and globalisation. Composed of chronologically broad and diverse case studies from colonial contexts, this book is for researchers in colonial and post-colonial archaeology as well as archaeological and cultural-historical numismatics"--